2006
DOI: 10.2341/05-19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air-drying Time of Single-application Self-etch Adhesives on Dentin Bond Strength

Abstract: This study examined the effect of air-drying time of adhesives on the dentin bond strength of several single-application self-etch adhesive systems. The adhesive/resin composite combinations used were: Adper Prompt L-Pop/Filtek Z250 (AP), Clearfil Tri-S Bond/Clearfil AP-X (CT), Fluoro Bond Shake One/Beautifil (FB), G-Bond/Gradia Direct (GB) and One-Up Bond F Plus/Palfique Estelite (OF). Bovine mandibular incisors were mounted in self-curing resin and wet ground with #600 SiC to expose labial dentin. Adhesives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…10,11,20,21) Water is essential in one-step self-etching systems to ionize acidic monomer enough to dissolve the smear layer and demineralize dentin.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,20,21) Water is essential in one-step self-etching systems to ionize acidic monomer enough to dissolve the smear layer and demineralize dentin.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly better bond strength with five-second air drying time in the agitation group could be related to better solvent evaporation and dispersion of water. 13 Better bonding with active agitation could be attributed to better removal of the smear layer, dispersal of fluid content and better diffusion of dentin primer into the collagen-rich partially-demineralized zone, which helps in achieving the micromechanical and chemical interaction with the underlying dentin. 10 Active agitation of self-etching bonding agents may improve bonding by enhancing the interaction of acid monomers with tooth structure and dispersing etching byproducts into the hybrid layer.…”
Section: Discussionmentioning
confidence: 99%
“…14 While Bonilla and others 15 reported maximum bond strength with a dry time of one second with both the self-etch and total-etch systems, Chiba and others 13 reported maximum bond strength with a dry time of five seconds with the self-etch systems. Furthermore, Miyazaki and others 10 found that drying time varied for two total-etch systems tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,[39][40][41][42] In addition to the material-specific parameters and equipment used, the variability in handling by the clinical operators plays an important role. 1,6,[43][44][45][46][47][48] Etch-and-rinse adhesives are considered to be partially technique-sensitive. 1 To overcome these challenges, simplified and user-friendly self-etch adhesives have been developed.…”
Section: Introductionmentioning
confidence: 99%